Entre homens e diabos: uma etnografia dos Guarani Nhandéva acometidos pelo jepotá - Santos, Jovane Gonçalves dos (2012)
This work presents my ethnographic research developed between the Guarani Nhandéva Indians from Tekohá Añetete Village. The village is located in the city of Diamante do Oeste Paraná State. The study has as its main theme the -jepotá , considered by the natives as a evil that turns men into animals and make them be recognized by their community, as people who embody the devil. In this context, the research aims to investigate if the ways how the Nhandéva understand and live with the -jepotá , are or are not formulated/ created from the mythology.